Penerapan pendekatan open-ended berbantuan program Microsoft Excel dalam pembelajaran matematika untuk meningkatkan kemampuan berpikir kreatif matematik peserta didik - Dedi Nurjamil; Vepi Apiati (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2015)
The era of globalization and competition requires the improvement and development of quality human resources. Competition era of globalization has been met by a wide range of advanced technologies. It is necessary to find an alternative learning which can improve learning activities and provide opportunities for learners to be more creative. One method of learning that can be done is the adoption of the Open-Ended Approach with Microsoft Excel program. The focus of this study was to determine the improvement in mathematical creative thinking abilities of learners towards learning mathematics. The population in this study were all students of class XI SMU 1 Tasikmalaya, and the samples were taken randomly from the entire classes. Two classes were selected as experimental class and control class. The instrument used consisted of testing the ability of creative thinking and mathematical model attitude Likert scale. The instrument used has been valid and reliable. The data has been analysed using the normalized gain test and statistical test such as t-test ‘and the Mann-Whitney test. The result has been shown the improvement of the ability to think creatively of mathematical learners by the Open-Ended approach Microsoft Excel program is better than learners by the Open-Ended approach without the assistance of Microsoft Excel Program. The attitude of learners towards learning with the Open-Ended approach with Microsoft Excel program is positive.